The Effect of Seaweed Carrageenan (Kappaphycus Alvarezii) Concentration on Vitamin C Content, Moisture Content, pH and Sensory Characteristics of Tomato Sauce - Naila Dwi Rahmasari; Andriyana Monica Sahidu; Ahmad Shofy Mubarak; Lailatul lutfiyah; Eka Saputra; Sri Subekti (Grouper, 2026)
Tomato sauce generally requires a thickening agent to improve its viscosity. Synthetic thickeners such as carboxymethyl cellulose (CMC) may increase pH, making them less suitable for meeting the quality requirements of tomato sauce, which is naturally acidic. This study aimed to evaluate seaweed carrageenan (Kappaphycus alvarezii) as a natural thickener and to determine the effect of different concentration levels on vitamin C content, moisture content, viscosity, pH, and sensory characteristics of tomato sauce. This study used a completely randomized design with five treatments and four replications, a positive control with 0.25% CMC, and carrageenan treatments at concentrations of 0.25%, 0.30%, and 0.35%, each with four replications. Chemical and physical parameters were analyzed using one-way ANOVA followed by Duncan’s multiple range test, while sensory evaluation data were analyzed using the Kruskal–Walli’s test followed by the Mann–Whitney test at a 95% confidence level. The results showed that increasing carrageenan concentration significantly increased vitamin C content and viscosity, while significantly reducing moisture content and pH (p < 0.05). The 0.35% carrageenan treatment produced the highest vitamin C content (4.00 mg/100 g), the lowest moisture content (70.63%), the highest viscosity (15.58 cPs), and a pH of 3.25. Sensory evaluation indicated that carrageenan significantly affected texture but had no significant effect on appearance, aroma, or taste. Carrageenan at a concentration of 0.35% was considered the optimal level for producing tomato sauce with the best physicochemical quality and texture while maintaining an appropriate pH range for tomato sauce.